Perioperative Renoprotection: General Mechanisms and Treatment Approaches. (December 2020) - Molinari, Luca; Sakhuja, Ankit; Kellum, John A.
Abstract : In the perioperative setting, acute kidney injury (AKI) is a frequent complication, and AKI itself is associated with adverse outcomes such as higher risk of chronic kidney disease and mortality. Various risk factors are associated with perioperative AKI, and identifying them is crucial to early interventions addressing modifiable risk and increasing monitoring for nonmodifiable risk. Different mechanisms are involved in the development of postoperative AKI, frequently picturing a multifactorial etiology. For these reasons, no single renoprotective strategy will be effective for all surgical patients, and efforts have been attempted to prevent kidney injury in different ways. Some renoprotective strategies and treatments have proven to be useful, some are no longer recommended because they are ineffective or even harmful, and some strategies are still under investigation to identify the best timing, setting, and patients for whom they could be beneficial. With this review, we aim to provide an overview of recent findings from studies examining epidemiology, risk factors, and mechanisms of perioperative AKI, as well as different renoprotective strategies and treatments presented in the literature.